2015
DOI: 10.1007/s00268-015-3311-2
|View full text |Cite
|
Sign up to set email alerts
|

Suture Versus Mesh Repair in Primary and Incisional Ventral Hernias: A Systematic Review and Meta‐Analysis

Abstract: Mesh repair reduces the number of recurrences significantly. In patients without recurrence mesh repairs seem to be associated with a risk of chronic pain especially if the mesh is fixed sublay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 33 publications
3
52
0
3
Order By: Relevance
“…Table 12 shows the characteristics of selected studies. The minimum and maximum reported values were respectively 2.4% [97] and 22.3% [80] for SAWR and 5% [75] and 24.3% [79] In the case of AWR the clinical visit is currently the choice. Every doubt can be confirmed by imaging.…”
Section: Awr -Recurrencementioning
confidence: 99%
“…Table 12 shows the characteristics of selected studies. The minimum and maximum reported values were respectively 2.4% [97] and 22.3% [80] for SAWR and 5% [75] and 24.3% [79] In the case of AWR the clinical visit is currently the choice. Every doubt can be confirmed by imaging.…”
Section: Awr -Recurrencementioning
confidence: 99%
“…Moreover, Venclauskas et al (18) reported recurrence rates of 10.5% using onlay mesh repair and 2% using sublay mesh repair. In a meta-analysis, Mathes et al (22) reported no difference in recurrence rates. Similarly, in the present study, the recurrence rates using onlay and sublay mesh repair techniques were found to be similar: 6% using onlay mesh repair and 2% using sublay mesh repair.…”
Section: Incisional Hernia Remains a Major Problem After Laparotomymentioning
confidence: 99%
“…[4][5][6] Although mesh reduces recurrences, it is a foreign material and may cause a host of complications. 7,8 These range from mild skin problems such as skin infections, nonhealing wounds, and seroma formation to severe chronic pain, lifethreatening bowel obstruction, and chronic fistula development that may be caused by chronic mesh infection.…”
mentioning
confidence: 99%